Getting ahead of the game: Experiential learning for groundwater governance in Ethiopia - ElDidi, Hagar; Zhang, Wei; Blackmore, Ivy; Gelaw, Fekadu; De Petris, Caterina; Teka, Natnael; Yimam, Seid; Mekonnen, Dawit Kelemework; Ringler, Claudia; Meinzen-Dick, Ruth S. (Ubiquity Press, Ltd., 2024)
Groundwater management is highly complex, with many users sharing the same resource often with limited understanding of their interconnectedness. Behavioral experiments (games) that simulate real-life common-pool resource use have shown promise as an experiential learning tool for improving resource governance. This study pilots an experiential learning intervention in Ethiopia using a groundwater game to help raise awareness of groundwater over-extraction and improve understanding of the importance of collective action in governance. In the Meki River catchment in Ethiopia, small-scale irrigation is expanding, but overextraction and competition over groundwater have not yet reached alarming levels. The groundwater game, adapted from India and including the addition of a rule-making round, was played in 15 villages with 30 groups. The game was accompanied by subsequent community-wide debriefing in each village to reflect on the experience and lessons learned, which stimulated discussions about groundwater governance. We surveyed participants to capture individual mental models regarding groundwater use and management, as well as any immediate learning effects. Focus group discussions in each village prior to the intervention and again six months after the intervention assessed possible lasting effects. The findings indicate cognitive, normative and relational learning, including increased understanding of groundwater dynamics (such as the joint effect of diverse water uses and users), the importance of collective action in resource management, and the benefits of communication. We find gendered differences in decision-making about resource extraction in the game and development of group-level resource management, confirming the need for gender-responsive approach to sustainable groundwater management interventions. We discuss community-wide learning and institution-building, and considerations for future intervention designs. We recommend embedding experiential learning, facilitated by local extension officers and other practitioners, in intervention packages that include both technical assistance on water-conserving technologies and groundwater management approaches and support in building communities’ institutional capacity.